2021
DOI: 10.32615/ps.2021.026
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of chlorophyll fluorescence transient measurements, using Handy PEA and FluorPen fluorometers

Abstract: Chl -chlorophyll; Fm -maximum Chl a fluorescence; Fo -initial (minimal) Chl a fluorescence; Fv (= Fm -Fo) -variable Chl a fluorescence; I-step -Chl a fluorescence at ~ 30 ms; J-step -Chl a fluorescence at ~ 2 ms; OJIP curve -the 'fast' phase of the fluorescence transient ['O' is for the initial fluorescence (at ~ zero time), 'P' is for peak, and 'J' and 'I' are inflection points between 'O' and 'P']; PQ -plastoquinone; QA and QB -the first and second plastoquinone electron acceptor of PSII. Acknowledgments: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Under these conditions, it has been reported that both thermo-tolerant and thermo-sensitive cucumber species show decreased leaf gas exchange parameters, but only thermo-tolerant cucumber species restore functions to a relatively healthy level after high-temperature exposure [32]. Nevertheless, A CO2 and g s reduction in treated plants could be due to an adaption mechanism to high light and temperature favoured by Archer ® Eclipse's application, since leaf damage was not observed and Fv/Fm, PIABS, RC/ABS, and ΨEO values were higher than in non-treated plants [15].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Under these conditions, it has been reported that both thermo-tolerant and thermo-sensitive cucumber species show decreased leaf gas exchange parameters, but only thermo-tolerant cucumber species restore functions to a relatively healthy level after high-temperature exposure [32]. Nevertheless, A CO2 and g s reduction in treated plants could be due to an adaption mechanism to high light and temperature favoured by Archer ® Eclipse's application, since leaf damage was not observed and Fv/Fm, PIABS, RC/ABS, and ΨEO values were higher than in non-treated plants [15].…”
Section: Discussionmentioning
confidence: 92%
“…The kinetics of Chl a fluorescence were determined using the Handy PEA Chlorophyll Fluorimeter (Hansatech Ltd., King's Lynn, Norfolk, UK); OJIP phases were induced by red light (650 nm), with a light intensity of 3000 µmol photons m −2 s −1 . OJIP fluorescence phases were analysed using the JIP test [15]. Measurements were performed on fully developed leaves at the mid-plant position of nine plants per treatment.…”
Section: Chl a Fluorescence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PSII functionality was assessed by the JIP test with a portable fluorimeter measure with red light (Handy-PEA, Hansatech, King's Lynn, UK), using the 50 µs fluorescence level as F 0 according to Strasser et al (2000Strasser et al ( , 2004. Although recent studies showed a better fitting of earlier F0 values to extrapolated 'true' F0 (e.g., 20 μs; Padhi et al 2021), we chose to use 50 μs as F0 to enable comparability with previous investigations on the same oak species (e.g., Bantis et al 2019Bantis et al , 2020Bantis et al , 2021Koller et al 2020).…”
Section: Gas-exchange Measurementsmentioning
confidence: 99%
“…are native to Greece, where they grow in the entire country (Strid and Tan 1997). On the contrary, Q. frainetto is not native to Germany and Q. pubescens is found only in limited locations in SW Germany (Bussotti et al 1998, Pasta et al 2016. Introducing seed material of these oak species from an Italian provenance in Greece would be equivalent to the approach of assisted population migration to enlarge the gene pool of the already existing species (Winder et al 2011).…”
Section: Introductionmentioning
confidence: 99%